2020
DOI: 10.1101/2020.09.16.299420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular DJ-1 induces sterile inflammation in the ischemic brain

Abstract: Inflammation is implicated in the onset and progression of various diseases, including cerebral pathologies. Here we report that DJ-1, which plays a role within cells as an antioxidant protein, functions as a damage-associated molecular pattern (DAMP), and triggers inflammation if released from dead cells into the extracellular space. We first found that recombinant DJ-1 protein induces the production of various inflammatory cytokines in bone marrow-derived macrophages (BMMs). We further identified a unique pe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Previous studies revealed that DJ-1 was involved in multiple biological functions in mammals (Hijioka et al, 2017; Scumaci et al, 2020; Mencke, 2021; Nakamura et al, 2021). However, DJ-1 regulation of sexual and asexual differentiation in mammals, plants and fungi was poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that DJ-1 was involved in multiple biological functions in mammals (Hijioka et al, 2017; Scumaci et al, 2020; Mencke, 2021; Nakamura et al, 2021). However, DJ-1 regulation of sexual and asexual differentiation in mammals, plants and fungi was poorly understood.…”
Section: Discussionmentioning
confidence: 99%